Contour milling programming technology for virtual basing on a CNC machine - Petrakov, Yuri; Shuplietsov, Danylo (Eastern-European Journal of Enterprise Technologies, 2019)
A new technique and an application program for automating the programming of the milling operation during virtual basing of the workpiece on the CNC machine table is presented, when precise installation of the workpiece along the coordinate axes of the machine is difficult. The solution of such a scientific and technical problem allows you to perform contour milling of parts with their arbitrary location on the table of the CNC machine with guaranteed alignment of the allowance along the forming path. The method involves the sequential implementation of three stages with parallel use of the created application program. At the first stage, an electronic copy of the part drawing is prepared, which contains the selected part and workpiece contour highlighted in different colors. Thus, the scanning provides automatic creation of digital two-dimensional arrays of geometric images necessary to solve the problem. At the second stage, the coordinates of three points of the workpiece measured by the probe on the machine are entered into the created program. Based on the entered data, the created program solves the problem of alignment of the allowance using the Gauss-Seidel method using the Hausdorff dimension. This approach allows us to obtain a quantitative estimate of the similarity of polygonal objects, which is necessary to solve the problem of minimax location of the allowance. The task is to determine the correction of the control program for two linear coordinates and one angular around the center of mass of the workpiece. At the third stage, the correction values calculated in the program are entered into the CNC rack of the machine and the processing of the contour begins. The proposed technique and the created application program were tested when processing the part contour on a VF-3 HAAS milling machine. Practical testing has shown the effectiveness of the technique, which is to ensure milling without overloading the tool and reduce the processing time during virtual basing of the workpiece